Cysticercosis Involving Muscle of Mastication: A Review and Report of Two Cases - Sarbjeet Singh; V. Sreenivasan; Kanika Garg; Nikhel Dev Wazir; Jaspal Singh Rajput; Pawandeep Sandhu Virk (Case Reports in Dentistry)
Cysticercosis is a parasitic infection caused by the larval stages of the parasitic cestode, Taenia solium. It is a common disease in developing countries where it is also endemic. The central nervous system (CNS) is the most important primary site of infection and the disease can present with solitary or multiple space occupying lesions. Cases of cysticercosis presenting as isolated muscle mass (pseudotumours) without involvement of the CNS have also been recently described in the literature. We present two cases who presented to us with pain, swelling, and tenderness involving the temporalis muscle along with trismus. Ultrasonography and MRI findings were suggestive of cysticercosis involving the temporalis muscle which resolved after the albendazole therapy.